2018
DOI: 10.1504/ijta.2018.096399
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle mobility: shifting conception of home in modern China

Abstract: The user has requested enhancement of the downloaded file.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In this case, customer satisfaction is reflected. According to Park and Noh (2018) and Zhu (2018), instant culture influence is a combination of satisfaction and perception of consumer social support. Due to high consumer mobility, people also want to consume instantly.…”
Section: Instant Cultural Responsementioning
confidence: 99%
See 1 more Smart Citation
“…In this case, customer satisfaction is reflected. According to Park and Noh (2018) and Zhu (2018), instant culture influence is a combination of satisfaction and perception of consumer social support. Due to high consumer mobility, people also want to consume instantly.…”
Section: Instant Cultural Responsementioning
confidence: 99%
“…Tripathi et al (2020) confirmed that people currently want convenience, comfort, and safety. Modern consumer societies look for alternative lifestyles to get instant gratification (Zhu, 2018).…”
Section: Introductionmentioning
confidence: 99%